PENINGKATAN EFISIENSI DAN KUALITAS PRODUKSI BLACK GARLIC PADA UMKM DE PAITON MELALUI PENGEMBANGAN TEKNOLOGI FERMENTASI BERBASIS IOT - Shofia Hattarina; Linda Kurnia S.; Elok Dwi Vidiastutik (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
The goal of this program is to increase the income of UMKM partners through high-value-added products (economic) by utilizing IoT technology and improving partner financial management with a digital bookkeeping application. The main problem in the black garlic production stage is the fermentation process, which still uses a rice cooker. The use of a rice cooker in the black garlic fermentation stage limits production, accommodating only 1-3 kg of garlic per session, and requires a longer fermentation time (14-40 days). The small capacity and long production time make it difficult to meet large market demand. Management challenges include manual and rudimentary bookkeeping. This is due to a lack of bookkeeping knowledge and partners finding it difficult. The result of this community service is that after using a fermentation machine with IoT technology, black garlic production capacity has increased. In terms of financial records, bookkeeping quality has improved after using digital bookkeeping.